FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN MAKANAN PERTAMA PADA BAYI SEBELUM USIA ENAM BULAN DI NEGERI ISU KECAMATAN TEON NILA SERUA - Asriaty Dinopawe; Elvandi Imlalay (Pasapua Health Journal, 2021)
Introduction: A healthy baby is every parent’s dream and to get a healthy baby parents need to monitor the growth and development of the baby which is very dependent on the nutrition provided. Providing nutrition to children through stages that are adapted to the baby’s digestive system. Infants aged 0-6 months should only be given breast milk (exclusive breastfeeding), but in fact our society has provided complementary food for breast milk (MP-ASI) to infants aged less than 6 months. (Ministry of Health RI, 2018). Breast milk (breast milk) is the only intake consumed by infants aged 0-6 months. Breast milk only meets the needs of babies around 70 percent in the age range 6-8 months, 50 percent in the age range 9-11 months and only 30 percent over one year. Method: The research design used in this research is a quantitative correlation research using a Cross Sectional Study approach. The population is 68 babies aged 1-5 years in the area of Negeri Issu Teon Nila Serua District. Results: The results showed that there was a relationship between knowledge and value (p=0.001). This data analysis uses the chi-square test. The results of this study were obtained from the P Value <0.05. Conclusion: that there is a relationship between knowledge.